A Novel Secure and Robust Watermarking of Medical Images Using SSVD (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital image watermarking is an effective methodology for the content to be authenticated, both for normal and medical images. Moreover, the progressive developments in internet users have significantly increased today. In addition to being undetectable to the human eyes, the image watermark should also be durable and trustworthy. This research enumerates the proposal of an enhanced methodology on the basis of Singular value decomposition (SVD) and Discrete wavelet transform (DWT) image water marking systems. The Shuffled SVD (SSVD) is considered as the default SVD-variable. Here, the DWT splits the images into 4 subbands (LL, HL, LH and HH). The LL subband is divided into equally sized blocks. Following application of SSVD in several block of the LL subband, the principal components of the watermark images were placed. From the simulation results, it was observed that, there is a greater resilience and a positive error in this proposed medical image watermarking system.